Development of Acetylcholine Receptor Clusters on Cultured Muscle Cells - Sytkowski, A. J. (1973)
Clusters of acetylcholine receptors were formed in the absence of neurons during the development of cultured chick-embryo skeletal muscle cells. The average concentration of receptors in clusters was estimated to be 9000 per μm(2). At other regions of the cell, receptor concentration was 900 per μm(2). The possibility that receptor clusters may participate in synapse formation is suggested.